2018
DOI: 10.1097/sla.0000000000002167
|View full text |Cite
|
Sign up to set email alerts
|

Oral Polyphosphate Suppresses Bacterial Collagenase Production and Prevents Anastomotic Leak Due to Serratia marcescens and Pseudomonas aeruginosa

Abstract: Polyphosphate administration may be an alternative approach to prevent anastomotic leak induced by collagenolytic bacteria with the advantage of preserving the intestinal microbiome and its colonization resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 43 publications
0
89
0
2
Order By: Relevance
“…Phosphate thus becomes one avenue of interaction between the microbes and the human host. Recent studies indicate that local depletion of phosphate in microbiome communities can cause major changes in member phenotypes than can adversely affect the health of the host . Critical illness, immunodeficiency, and medical interventions to treat human disease disrupt the normal intestinal microbiome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphate thus becomes one avenue of interaction between the microbes and the human host. Recent studies indicate that local depletion of phosphate in microbiome communities can cause major changes in member phenotypes than can adversely affect the health of the host . Critical illness, immunodeficiency, and medical interventions to treat human disease disrupt the normal intestinal microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that phosphate becomes depleted in the intestinal tract following surgical injury and is a major “cue” that triggers bacterial virulence . Furthermore, in vitro and in vivo studies indicate that the maintenance of phosphate abundance prevents Pseudomonas aeruginosa virulence expression and that sodium hexametaphosphate attenuates collagenolytic activity and biofilm production in vitro and prevents anastomotic abscess formation and gross leak in mice after anastomotic exposure to Serratia marcescens and P. aeruginosa . While oral administration of phosphates is viable, it requires high concentrations to properly increase phosphate concentration in the colon.…”
Section: Introductionmentioning
confidence: 99%
“…We performed this very series of experiments in a rat model of anastomotic leak and provided the necessary molecular detail to confirm that two intestinal microbes ( P. aeruginosa, E faecalis ) can fulfill these criteria as primary causative agents in anastomotic leak pathogenesis (65, 66). Most recently we identified yet a third organism capable of causing leak, Serratia marcescens (69). …”
Section: The Pathogenesis Of Al Is Likely To Be More Complex Than Is mentioning
confidence: 99%
“…Both at the level of the wound and anastomosis, there is compelling evidence that preservation of the normal microbiota is highly beneficial to healing (49, 82, 83). It seems time that we begin to understand which microbes should be preserved to promote healing and which should be “controlled” rather than eliminated in order to prevent infection (69). As our predecessors predicted about the nature of pathogens whose virulence is conditionally activated, “it is not necessary to kill them in order to make them relatively harmless (13).…”
Section: Using Microbiome Sciences To Develop “Bowel Prep 20”mentioning
confidence: 99%
“…In these situations, the gastrointestinal tract becomes a hostile and nutrient‐scarce environment which activates colonized hospital pathogens to express virulent phenotypes and cause life‐threatening inflammation, in a process commonly known as sepsis . Currently, the treatment to prevent proliferation of such pathogenic bacteria is through oral supplementation of antibiotics . However, this practice often leads to further complications as this results in the elimination of normal intestinal microbiota and its replacement with multi‐drug resistance and potentially virulent associated pathogens …”
Section: Introductionmentioning
confidence: 99%